Regulating glucose metabolism using nanomedicines for cancer therapy. Issue 29 (1st July 2021) - Tang, Ming; Ren, Xiangling; Fu, Changhui; Ding, Minghui; Meng, Xianwei
Abstract : The application of glucose metabolism regulation with nanomedicine in cancer therapy. Abstract : The regulation of glucose metabolism is a research focus in cancer treatment. Glucose metabolism is essential for maintaining the growth and proliferation of tumor cells, thus offering us great opportunities for tumor treatment. Recently, much progress has been made in efficient cancer treatment by regulating the pathway of glucose metabolism with nanomedicines due to the rapid development of nanotechnology and promising drug targets. In this review, we first introduced the pathway of cell energy supply from the perspective of aerobic and anaerobic processes. Then, we discussed the recent research progress in regulating glucose metabolism for various tumor resistance strategies including heat resistance, multiple drug resistance, and hypoxia. Finally, we presented the prospects and challenges of developing multifunctional nanoagents for efficient chemotherapy, hyperthermia, dynamic therapy and so on by regulating glucose metabolism.